Dragon blood resin ameliorates steroid-induced osteonecrosis of femoral head through osteoclastic pathways - Yuhao Liu; Liang Mo; Hongduo Lu; Yangwenxiang Wei; Jiahao Zhang; Samuel Bennett; Jiake Xu; Jiake Xu; Chi Zhou; Bin Fang; Zhenqiu Chen (Frontiers in Cell and Developmental Biology, 2023)
Objective: Dragon’s Blood resin (DBR) is a traditional medicinal substance renowned for its diverse pharmacological effects, which consists of potent anti-inflammatory, antioxidant and angiogenic properties. This study aimed to elucidate its therapeutic mechanism in alleviating steroid-induced osteonecrosis of the femoral head (SIONFH).Methods: Techniques such as SPR and LC-MS were employed to identify and analyze the target proteins of DBR in bone marrow macrophages (BMMs). In vitro, BMMs were treated with RANKL and DBR, and TRAcP staining and actin belt staining were utilized to assess osteoclast activity. The inhibitory effects and underlying mechanisms of DBR on osteoclastogenesis and reactive oxygen species (ROS) generation were determined using real-time PCR, western blotting and immunofluorescence staining. An in vivo SIONFH rat model was set up to assess the curative impacts of DBR using micro-CT scanning and pathological staining.Results: Bioinformatic tools revealed a pivotal role of osteoclast differentiation in SIONFH. Proteomic analysis identified 164 proteins binding in BMMs. In vitro assessments demonstrated that DBR hindered osteoclastogenesis by modulating the expression of specific genes and proteins, along with antioxidant proteins including TRX1 and Glutathione Reductase. Notably, the resin effectively inhibited the expression of crucial proteins, such as the phosphorylation of JNK and the nuclear localization of p65 within the TRAF6/JNK and NFκB signaling pathways. In vivo experiments further confirmed that DBR mitigated the onset of SIONFH in rats by curbing osteoclast and ROS activities.Conclusion: These findings underscore the potential of Dragon’s Blood as an effective administration for early-stage SIONFH, shedding light on its therapeutic influence on ROS-mediated osteoclastic signaling pathways.